TREATMENT OUTCOME EVALUATION OF TB PATIENTS COMPARED TO TB-HIV PATIENTS AT SARDJITO GENERAL HOSPITAL FROM 2009 TO 2012 - , SYUHADA DERMAWAN ARIFIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. TB was a huge global problem in the world, including Indonesia with increasing the new cases evidence every year. HIV was one the fastest development disease in the world including Indonesia. HIV co-infection in TB was one most common infection. Objective. To evaluate the treatment outcome of TB without HIV patients compared to TB with HIV patients. Method. The study was retrospective cohort study involved patients (age > 18 years) with diagnosed TB, administered to Sardjito Hospital from 2009-2012. The dependent variable was favorable which were cure , complete and unfavorable which were default, failure, referred, dead. The independent variable was HIV co-infection. Result. The relative risk result is 2.65 with 95% CI(1.28 to 5.49) for unfavorable outcome in TB with HIV positive patients. Conclusion. TB with HIV patients tend to have more unfavorable outcome of treatment two times higher compared to TB without HIV patients.